Uji Stabilitas Masker Gel Peel Off Kombinasi Sisik Ikan Bandeng Dan Kulit Jeruk Nipis - Cikra Ikhda Nur Hamida Safitri; Cahya Tri Miftakhul Jhanna (Calory Journal Medical Laboratory Journal, 2024)
The lime plant with the Latin name Citrus Aurantifolia is a plant that grows widely in Indonesia. Lime can also be used as a cough medicine, phlegm buster, influenza medicine, acne medicine and many more. Apart from using natural materials, we also use fish scale waste. Milkfish scales contain 0.3% collagen. The collagen content can be used as anti-aging for the skin. To find out the stability test of the peel off gel mask, a combination of milkfish scales and lime, meets the criteria parameters for cosmetic preparations. The formulation of the peel off gel mask was carried out by modifying the formula into 3 (three) formulas with different concentrations of the extract to be used, namely F1 (1%), F2 (3%) and F3 (5%). This research began with collecting simplicia, extraction, making a peel-off gel mask and stability testing. The stability tests carried out were organoleptic, pH, dry preparation time and spreadability. In accordance with SNI masks 16-6070-1999. The stability test of the preparation was determined by storing the preparation for 21 days at different temperatures. The stability test is based on looking at the changes that occur starting from day 1 to day 21 of storage. The test results of the three peel-off gel mask formulations showed that the three temperatures on day 21 experienced changes in test parameters. The research results were analyzed using the SPSS Anova method.